Myocardial Functions of Children with Acute Poststreptococcal Glomerulonephritis - Balat, A; Baysal, K; Kocak, H (Dustri-Verlag Dr Karl Feistle, 1993)
Left ventricular function was investigated by two-dimensional and M-mode echocardiography in 35 patients with acute poststreptococcal glomerulonephritis and in 25 healthy controls. Six of these patients were found to have myocardial dysfunction during the acute congestive phase and convalescent phases of APSGN. One of these 6 patients, later, died. No correlations were determined between myocardial dysfunction and hypertension, cardiac failure, pericardial and pleural effusion. As a result, left ventricular function may be impaired in acute congestive phase of APSGN and this may affect the course and prognosis of the disease.
Keywords: Acute Poststreptococcal Glomerulonephritis; Echocardiography; Left Ventricular Function